Fotoconversão de CO2 em produtos com valor agregado - Faria, Ana Luiza Alves (2021)
In recent decades, due to population and industrial growth, the energy demand has increased significantly. However, much of the energy consumed comes from burning fossil fuels, which emit large amounts of gases that can increase the temperature of the earth. Among these gases, carbon dioxide (CO2) stands out as one of the main causes of the greenhouse effect. Thus, the need to develop new economically and energetically viable technologies for energy production through clean and sustainable routes is essential. Among these technologies, the CO2 photoconversion process (“artificial photosynthesis”) in products with added value can be highlighted. However, the vast majority of semiconductors developed to date, for this purpose, have a high rate of recombination of their photogenerated electron/hole pairs, thus reducing the efficiency of the process. In order to improve the photocatalytic efficiency, this project aimed to develop semiconductors based on niobium pentoxide (Nb2O5) modified with iron (Fe) or copper (Cu) for photoreduction of CO2, aiming to increase the photocatalytic efficiency of the material through the reduction in the rate of recombination of the photogenerated electron/hole pairs. For this, semiconductors based on Nb2O5 were synthesized by the oxidizing peroxide method under hydrothermal treatment. The depositions of Fe or Cu were carried out by the method of sputtering ("magnetron sputtering") since this technique allows the deposition of nanoparticles with a high degree of purity. The addition of Fe or Cu nanoparticles on the Nb2O5 surface significantly reduced the rate of recombination of the photogenerated electron/hole pairs, due to the greater spatial separation of the photogenerated charges through the formation of heterostructure between the materials, which resulted in a significant increase in CO2 photoconversion. The materials modified with Fe showed high production of carbon monoxide (CO) (356.6 µmol/g). In addition, the calcination of the Nb2O5 semiconductor and its modification with Fe favored the production of methane (5.13 µmol/g), methanol (75.78 µmol/g) and acetic acid (69.07 µmol/g). On the other hand, Cu-modified materials showed a high production of methane (52.5 µmol/g) and methanol (628.01 µmol/g), compared to Nb2O5 and the catalysts modified with Fe The higher conversion efficiency for materials modified with Cu is related to the ability of Cu to trap the photogenerated electrons in the conduction band of Nb2O5.